Distributed Ledger Technologies and Prospects of Their Use in the Education System - D. A. Kachan (Цифровая трансформация, 2019)
The article discusses the features of distributed ledger technology based on the use of decentralized peer-topeer networks. The history of the emergence and development of distributed ledger technology considered in detail, the prerequisites for the growth of its popularity in various fields are analyzed. The main advantages and disadvantages of distributed ledger technology in general, as well as decentralized (permissionless) and exclusive (permitted) blockchain platforms in particular, are revealed. The principles of functioning of cryptocurrencies on the basis of blockchain technology, including their issue (coinage) are described. The state of blockchain technologies from the point of view of technology maturity is considered. The main trends in the development of blockchain technology at the present stage are revealed. An analysis of the possibilities of using distributed ledger technology of public administration, including in the education system, in order to improve the safety and automation of functions is presented.